2007
DOI: 10.1523/jneurosci.0699-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Adenylyl Cyclase 3 Perturbs Peripheral Olfactory Projections in Mice

Abstract: A remarkable feature of peripheral olfactory projections in mammals is the convergence of axons from olfactory sensory neurons (OSNs) expressing the same odorant receptor (OR) into the same glomeruli. There is mounting evidence that the ORs play critical roles in glomerular formation. However, it remains unclear how the OR exerts its function of sorting axons into homogeneity. We and others have shown previously that activation of the G-protein/cAMP signaling cascade underlies glomerular formation. Here, we fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 48 publications
7
108
0
Order By: Relevance
“…Altered cAMP signaling, in turn, results in transcriptional dysregulation of neuronal guidance proteins and may also affect locally the behavior of the growth cones in response to external repulsive or attractive cues. These results are in line with recent findings implicating cAMP in the regulation of axonal pathfinding (29,39) as well as dendrite formation (40) and provide strong support for altered (increased) neuronal cAMP signaling due to a bona fide SCHZ risk mutation. Notably, we have recently reported an association between SCHZ and gain of function mutations in the VIPR2 locus (41) and showed that these mutations also enhance cAMP signaling in lymphocytes of patients.…”
Section: Discussionsupporting
confidence: 90%
“…Altered cAMP signaling, in turn, results in transcriptional dysregulation of neuronal guidance proteins and may also affect locally the behavior of the growth cones in response to external repulsive or attractive cues. These results are in line with recent findings implicating cAMP in the regulation of axonal pathfinding (29,39) as well as dendrite formation (40) and provide strong support for altered (increased) neuronal cAMP signaling due to a bona fide SCHZ risk mutation. Notably, we have recently reported an association between SCHZ and gain of function mutations in the VIPR2 locus (41) and showed that these mutations also enhance cAMP signaling in lymphocytes of patients.…”
Section: Discussionsupporting
confidence: 90%
“…The expression of this enzyme depends on neuronal activity and was severely reduced in the olfactory bulb of anosmic Cnga2 -/y mice 30 . OSN axon coalescence on glomeruli is perturbed in mice lacking functional CNG channels 31 or the adenylate cyclase 32 . We detected no obvious change in axonal convergence for OSNs expressing either the P2 or M72 receptor 31 (Fig.…”
Section: No Change Of Key Proteins and Axonal Convergencementioning
confidence: 99%
“…Because the olfactory signaling machinery is expressed in several segments of the renal epithelium, we assayed renal function in mice null for a necessary component of the olfaction pathway (AC3). AC3 Ϫ/Ϫ mice have been studied previously (2,5,7,16,17), and are known to be anosmic (unable to smell) and to have a very high fatality rate after birth. It is believed that the neonatal mortality is due to the inability of the pups to smell their mother, compromising their ability to nurse.…”
Section: Ac3 and Golfmentioning
confidence: 99%